Voltage control of AC hybrid microgrid - Pranay Kumar Panda; Abhisek Sahoo; Asutosh Samal; Debani Prasad Mishra; Surender Reddy Salkuti (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The decline of competence effectuated by the unreplenishable energy etymology due to the plummet of fossil fuels has created an alternate need for renewable energy sources to play a vital role in providing power at a larger scale. Thus, a new system of distribution of energy resources is introduced to tackle the ever-growing demand for power and safety of the environment using renewable energy sources with the traditional ways of transmitting power. Such challenges can be overcome by using hybrid microgrids which helps in detecting and hegemonizing faults more dexterously sanctioning sharing of load and instinctive switching through various algorithms thus improving the system accuracy and adaptability. This exertion incorporates the modeling of an AC hybrid microgrid system analyzed in the is-landed mode. Fuel stack and the photo-voltaic cell are used as renewable energy power sources. It also includes the PID control method to the solution the most encountered problems in a microgrid. The engaged control modus operandi can modulate and regulate the output voltage at an expected and paradigm value. The whole AC hybrid microgrid and its control are simulated in MATLAB/simulink R2020b.